Contemporary Challenges in Securing Human Rights - Lennox, Corinne (Open access titles, 2020)
To celebrate the 20th anniversary of the MA in Understanding and Securing Human Rights offered at the School of Advanced Study, University of London, we are pleased to publish a commemorative edited volume on human rights themes authored by distinguished alumni and faculty. The chapters reflect on cutting-edge challenges in the field of human rights. Topics include refugee protection, women's human rights, business and human rights, the role of national and international legal mechanisms and emerging themes such as tax justice, rights in the digital age, theories of change, and poetry. It is a credit to the MA programme that the chapters are rich with critical analysis, diverse expertise and innovative approaches. This book will be essential reading for students of human rights and practitioners who can benefit from the insights into theory and practice offered here.